2000
DOI: 10.1080/080352500750027899
|View full text |Cite
|
Sign up to set email alerts
|

Altering the NICU and measuring infants' responses

Abstract: This study demonstrates that Quiet periods are feasible for infants undergoing neonatal intensive care. The NICU environment was altered significantly for light, noise, infant handling and staff activity for a specified time period. These changes were associated with a reduced median diastolic blood pressure and mean arterial pressure and a decrease in infant movements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 0 publications
2
37
0
7
Order By: Relevance
“…Utilizar o programa de educação continuada para sensibilizar a equipe quanto aos efeitos do ruído ambiental (HASLAM, 1970;PARRADO;COSTA FILHO, 1992;SÁNCHEZ;SÁNCHEZ;GONZÁLES, 1996;GUIMARÃES et al, 1996;SLEVIN et al, 2000;DIAS, 2001), aplicando-o junto à clientela, visitantes, pais e também à própria equipe, seja por meio de palestras, debates ou livretos ilustrativos (LICHTIG; MAKI, 1992;NOLTE;DORFLING, 1995;. Incluir, ainda, dinâmicas de grupo para simular situações do cotidiano do trabalho, geradoras de ruídos intensos, os quais devem ser simultaneamente mensurados pelos participantes.…”
Section: ____________________________________________________________unclassified
“…Utilizar o programa de educação continuada para sensibilizar a equipe quanto aos efeitos do ruído ambiental (HASLAM, 1970;PARRADO;COSTA FILHO, 1992;SÁNCHEZ;SÁNCHEZ;GONZÁLES, 1996;GUIMARÃES et al, 1996;SLEVIN et al, 2000;DIAS, 2001), aplicando-o junto à clientela, visitantes, pais e também à própria equipe, seja por meio de palestras, debates ou livretos ilustrativos (LICHTIG; MAKI, 1992;NOLTE;DORFLING, 1995;. Incluir, ainda, dinâmicas de grupo para simular situações do cotidiano do trabalho, geradoras de ruídos intensos, os quais devem ser simultaneamente mensurados pelos participantes.…”
Section: ____________________________________________________________unclassified
“…Three studies filmed 3 set periods for 1 hour (8) or 2 hours (9,10) . The filming of infants for a 24-hour period has also been used in 4 other studies (1,(4)(5)(6)(7) , 1 of which occurred over different 24-hours periods over a span of 4 days (6) .…”
Section: Discussionmentioning
confidence: 99%
“…We identified 10 studies that have investigated infant manipulation, four of which (1,(4)(5)(6)(7) measured the nature and frequency of the manipulation and three of which (8)(9)(10) evaluated the implementation of a protocol, such as minimal touch, kinesthetic stimulation and gentle touch. The remaining three studies (11)(12)(13) addressed the pain to which the infant was subjected when manipulated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Several studies suggest that modifications of the care practices that reduce the stress and pain experienced by infants improve their clinical and neurobehavioral functioning. [5][6][7] However, not all studies have demonstrated beneficial effects of developmental care. [8][9][10] One possible reason for a lack of consistent findings is that, even though a NICU ascribes to carrying out developmental care, the actual level of developmental care may vary among different NICUs or over time.…”
mentioning
confidence: 99%